Who Consumes Firm Disclosures? Evidence from Earnings Conference Calls - Heinrichs, Anne; Park, Jihwon; Soltes, Eugene F. (The Accounting Review, 2019)
ABSTRACT Using a set of proprietary records, we examine who consumes quarterly earnings conference calls and under which circumstances the calls are consumed. While there is significant interest in calls by institutional investors and sell-side analysts, we find that investors who do not hold a position in the firm are a leading consumer. We show that buy-side non-holders who consume calls are more likely to hold positions in competitors and to purchase the stock in the future. In addition, many investors who hold large positions only consume calls periodically. We also document a benefit of consuming calls by finding that the consumption of calls is associated with more informed trading decisions. Overall, our investigation illuminates the actual consumption of conference calls by different consumers and the potential benefits of consuming additional firm disclosures.